Cover Picture: Biosynthesis of the Halogenated Mycotoxin Aspirochlorine in Koji Mold Involves a Cryptic Amino Acid Conversion (Angew. Chem. Int. Ed. 49/2014). Issue 49 (22nd October 2014) - Chankhamjon, Pranatchareeya; Boettger‐Schmidt, Daniela; Scherlach, Kirstin; Urbansky, Barbara; Lackner, Gerald; Kalb, Daniel; Dahse, Hans‐Martin; Hoffmeister, Dirk; Hertweck, Christian
<x xml:space="preserve">Abstract</x> The Koji Mold Aspergillus oryzae , which is widely used in food fermentations (e.g., sake production), produces the toxin aspirochlorine. C. Hertweck et al. elucidated in their Communication on page 13409 ff. the biosynthetic pathway of this chlorinated epipolythiodioxopiperazine. An iterative non‐ribosomal peptide synthetase assembles the diketopiperazine core from two phenylalanine units, one of which then undergoes an unprecedented conversion to glycine. Enzymatic halogenation of the second Phe unit significantly contributes to the biological activity of aspirochlorine.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>